Aerobic C–C and C–O bond formation reactions mediated by high-valent nickel species. Issue 44 (27th September 2019) - Smith, Sofia M.; Planas, Oriol; Gómez, Laura; Rath, Nigam P.; Ribas, Xavi; Mirica, Liviu M.
Abstract : Reported herein are organometallic Ni(ii ) complexes that react with mild oxidants such as O2 and H2 O2 and exhibit oxidatively-induced reactivity to yield C–C and C–O bond formation products via observable high-valent Ni intermediates. Abstract : Nickel complexes have been widely employed as catalysts in C–C and C–heteroatom bond formation reactions. While Ni(0), Ni(i ), and Ni(ii ) intermediates are most relevant in these transformations, recently Ni(iii ) and Ni(iv ) species have also been proposed to play a role in catalysis. Reported herein is the synthesis, detailed characterization, and reactivity of a series of Ni(ii ) and Ni(iii ) metallacycle complexes stabilized by tetradentate pyridinophane ligands with various N-substituents. Interestingly, while the oxidation of the Ni(ii ) complexes with various other oxidants led to exclusive C–C bond formation in very good yields, the use of O2 or H2 O2 as oxidants led to formation of appreciable amounts of C–O bond formation products, especially for the Ni(ii ) complex supported by an asymmetric pyridinophane ligand containing one tosyl N-substituent. Moreover, cryo-ESI-MS studies support the formation of several high-valent Ni species as key intermediates in this uncommon Ni-mediated oxygenase-type chemistry.